A new indirect immunofluorescence BIOCHIP method for the serological diagnosis of bullous pemphigoid: A review of literature. (9th April 2019) - Yang, Anes; Xuan, Rachel; Murrell, Dedee F
Abstract: The BIOCHIP (Dermatology Mosaic 7, EUROIMMUN, Lubeck, Germany) is a novel multiplex indirect immunofluorescence technique used in the serological diagnosis of bullous pemphigoid. The BIOCHIP method combines the screening of several autoantibodies and target antigen‐specific substrates in a single miniature incubation field to allow for simultaneous processing of the most common autoimmune bullous diseases autoantibodies using a single investigation. This manuscript reviews the literature on the validity of the BIOCHIP in the diagnosis of bullous pemphigoid. A systematic search for journal articles comparing the sensitivity and specificity of diagnostic tests for bullous pemphigoid patients was conducted in online databases via the Ovid SP search interfaces. The literature search generated 745 articles of which 189 were deemed relevant. Among the relevant articles, seven studies investigated the validity of the BIOCHIP indirect immunofluorescent test in the diagnosis of bullous pemphigoid. The BIOCHIP has demonstrated itself to be a specific test for BP180 (96.5–100%) and BP230 (98.3–100%), with a high sensitivity for BP180 (83.3–100%) but poor sensitivity for BP230 (24.3–66.7%). The BIOCHIP mosaic‐based immunofluorescence test is potentially a simple, time‐ and effort‐saving test that can aid in the diagnosis and screening of bullous pemphigoid. Further studies should report on the inter‐rater reliability of the BIOCHIP to further validate the tool.